Why Integrity? Why Now? - Edwin C. Constable (CHIMIA)
This article introduces scientific and research integrity, with a particular emphasis on its implications for the active chemical community in Switzerland. It attempts to equate research integrity to good scientific practice and presents this as benefiting the researcher, the institution, and the discipline. The concepts are developed, and current and future challenges are identified.